Biomechanics study on running shoes with different mechanical properties - Tang, Nicholas Jun Heng (Nanyang Technological University, 2021)
There is a variety of footwear testing methods that have been in use to design athletic footwear, with mechanical and biomechanical testing being the two most common types of testing. Biomechanical testing is the recruitment of participants into a series of experiments to collect data and analyse a shoe’s properties. To save time and reduce costs, mechanical testing was used in place of biomechanical testing. The earliest and simplest method was static shore hardness tests, a form of mechanical testing that measures the hardness of a shoe’s midsole. Based on intuition, having softer midsoles would improve shock absorption capabilities that will lead to lower loading rates acting on the athlete’s foot. High mean loading rates experienced has largely been associated with increased injury risks, thus it is important to be able to accurately test a footwear’s shock absorption properties. However, in the late 1990s, a new form of mechanical testing, the dynamic impact test (ASTM F1976), was introduced because of discrepancies with static shore hardness tests. One widely accepted reason for the discrepancies was that static shore hardness tests do not consider the stiffening effects of an ankle joint that occurs when the lower limb reacts to midsoles of varying hardness. This stiffening effect explains why there is an increase in loading rates even though the midsole is softer. In this study, a dynamic impact test and two kinds of biomechanical experiments (Brisk-Walking & Vertical Drop-Jump) were conducted on four pairs of running shoes of different midsole characteristics. The results obtained from all tests show that there is no observable relationship between dynamic impact tests and biomechanical tests. This is because the dynamic impact test rig is incapable of mimicking the mechanical properties of a human’s lower limbs. Therefore, the dynamic impact test rig needs to be improved upon before it can be used as a replacement for biomechanical testing.